Infective endocarditis in children with congenital heart disease: comparison of selected features in patients with surgical correction or palliation and those without. Issue 1 (July 1987) - Karl, T; Wensley, D; Stark, J; de Leval, M; Rees, P; Taylor, J F
Abstract : The diagnostic and prognostic features of 44 episodes of infective endocarditis in 42 children with congenital heart disease were reviewed. Endocarditis occurred in 18 patients who had not had surgical correction or palliation of the defect (non-operated group). There were 26 episodes in 24 patients who had been treated surgically (operated group) (16 open and eight closed cardiac operations). Endocarditis occurred soon after open heart surgery in eight patients and as a late complication in the other 16. It recurred in two patients (operated group). Invasive monitoring and low cardiac output were consistent features in those patients who had endocarditis soon after open heart surgery whereas dental treatment was a common feature in non-operated cases and after closed cardiac operations. Late cases of endocarditis after open heart surgery had various microbiological features that were not typical of infection after dental problems. Gram positive infections occurred in non-operated patients and in those who had had closed cardiac operations. The group that had open heart surgery had infections caused by Gram positive, Gram negative, and anaerobic bacteria and fungi. Fever, anaemia, leucocytosis, and positive blood cultures were the only consistent findings. Vegetations were seen in nine of 12 patients at cross sectional echocardiography. All 12 (four non-operated, one closed, and seven open cases) needed acute surgical treatment. The mortality from infective endocarditis was 17% for non-operated cases, 0% for those who had had closed heart surgery, and 50% for those who had had open heart surgery. Infective endocarditis after open heart surgery differs from that in the other subgroups in terms of microbiology, source of infection, and outcome and its early diagnosis depends on a thorough investigation of minimal symptoms and signs.